Eletronic begging and its social and economic impact on Jordanian society from the point of view of a sample of Facebook users - Alhashlamoun, Rania Mohammad Atia (Journal of Humanities & Social Sciences, 2021)
The wrong exploitation of the technological revolution left many of the crimes that we are witnessing their continuous increase, specifically financial ones. This study aimed to try to identify the phenomenon of electronic begging and its social and economic impact on Jordanian society, and to propose appropriate solutions to mitigate its exacerbation in the future, and the descriptive approach was used. Analytical description and analysis of this economic and social phenomenon. The electronic questionnaire was used to collect data and it was distributed to 500 The study sample was chosen by a simple randomized method, respondents who were exposed to electronic begging through social or cultural groups within Facebook. The results of the research concluded that electronic begging has negative effects on the national economy, And on society in general, so that it weakens confidence in the real need, and reduces social solidarity, and among the most prominent negative economic effects is the lack of a beggar’s contribution to the gross domestic product, as it represents a burden on society and helps to increase crime rates and impede economic growth, One of the most prominent recommendations of the study was to make leaflets to educate users of communication sites and businessmen of the danger of the spread of electronic begging.